Awareness on Hazard Analysis and Critical Control Points (HACCP) Principles in TVET and University Hospitality Schools in Kenya (International Journal of Scientific Research and Management (IJSRM), 2019)
The purpose of this study was to assess the level of awareness on Hazard Analysis and Critical Control Points (HACCP) principles in TIVET and University hospital schools in Kenya. A total of 671 respondents participated in the study (Comprising 249 from universities, 250 from Institutes of Technology, 64 from Polytechnics and 128 from Technical Institutions). Primary data sources included using structured questionnaires, taking photographs, oral interviews, observation check list and focus group discussions. Secondary sources, on the other hand, involved retrieving information from desk research where journals, books and other relevant literature were obtained. Both descriptive and inferential statistics were used to analyze the quantitative data while content analysis was used to analyze the qualitative data. The analyzed data were presented in terms of graphs and tables. The study found that 83% of the respondents interviewed were aware of the HACCP principles while 17% were not aware. The study revealed that (45%) respondents from Universities were aware of food safety and hygienic practices compared to respondents from TVET colleges at (38%). In testing the independence of institution category on awareness, the test yielded a p-value = 0.001, which was less than 0.05. Since the p-value was less than the level of significance, the null hypothesis of independence was rejected. This decision implied that there was a significant relationship between institution category and code of practice on awareness. The study concluded that even though the majority of the respondents indicated that they were aware of HACCP principles and food safety, they did not practice what they knew. It was recommended that there is need to create more awareness on HACCP principles and for food safety by holding workshops, seminars and sensitization programme to the stakeholders of hospitality industry